Piping design handbook - McKetta, John J. (Marcel Dekker, 1992)
This encyclopedic volume covers almost every phase of piping design - presenting procedures in a straightforward way.;Written by 82 world experts in the field, the Piping Design Handbook: details the basic principles of piping design; explores pipeline shortcut methods in an in-depth manner; and presents expanded rules of thumb for the piping design engineer.;Generously illustrated with over 1575 figures, display equations, and tables, the Piping Design Handbook is for chemical, mechanical, process, and equipment design engineers.